"Emotionscapes of geopolitics": Interpreting in the United Nations Security Council. Issue 1 (11th May 2021) - Jones, Alun
Abstract: The agency of interpreters has been kept out of view in human geography. This paper corrects this by focusing on embodied interpretation: bodies, freighted with their own relations, expectations, and experiences in the context of "emotionscapes, " settings for emotional communication. Conceptually, "emotionscapes" enable the exploration of the potentiality of an emotion in its spatial setting. Emotionally expressive behaviour is a process of the emotion; a potentiality to be realised. Emotions are distinctively connected to specific sites and spaces. This potentiality shifts the analytical focus away from what emotion is to what emotion can do to the alteration or reproduction of relations. I argue that this is vitally important to understanding geopolitical exchange, that is, how global politics is made and remade. However, the potentiality of emotions is made more complicated when interpretive bodies are involved in geopolitical exchange. They are intrinsic to the relational fluxes, currents, and flows of emotion – its potentialities – they identify and relay emotionally laden language of others for others in geopolitical communication. They observe, relay, and mutate emotional potentiality in "emotionscapes." In doing so, they wrestle with more than just words. They seek to capture emotions and geopolitics between real‐life people in real places. Understanding their endeavour should challenge us therefore to [re]consider geopolitical exchange in "emotionscapes" and the mediatory and performative roles played by interpretive bodies in these spaces of geopolitical knowledge production. This is my key purpose in this paper. Underpinning the paper's conceptual ideas are qualitative data on the role of interpretive bodies in realising emotional potentialities in the "emotionscape" of the UN Security Council in New York, arguably the most high‐profile geopolitical institution. Abstract : This paper provides a study of emotions and their capture in the UN Security Council through the new conceptual lens of "emotionscapes."